A flexible transparent colorimetric wrist strap sensor. Issue 2 (20th December 2016) - Wang, Ting; Guo, Yunlong; Wan, Pengbo; Sun, Xiaoming; Zhang, Han; Yu, Zhongzhen; Chen, Xiaodong
Abstract : A flexible transparent colorimetric wrist strap sensor device is developed as a smart wearable device for vivid color change sensing upon vapor exposure. Abstract : A flexible, transparent, and portable wrist strap sensor device has been well developed from a hierarchical polydiacetylene/MoS2 nanocomposite (PDA/MoS2 ) film. MoS2 with a nanoflake structure and chelation ability acts as a supporter for PDA films to enhance the porosity as well as the transparency of films, which increases the sensitivity, selectivity, and application potential of a PDA sensor. The PDA/MoS2 film sensor shows a linear detection range for N, N -dimethylformamide (DMF) vapor from 0.01% to 4% with a visible blue to red color change detected by the naked eye, which is more sensitive than other organic vapors. Exploiting the high transparency, vivid color change, remarkable flexibility and reliability, a wearable wrist strap sensor device with visible DMF sensing ability is fabricated based on PDA/MoS2 films, indicating their great potential for smart wearable devices.